New configurations of power converters for grid interconnection systems - Rivera, Marco; Toleda, Sergio; Nasir, Usman; Costabeber, Alessando; Wheeler, Patrick (2016)
The increased penetration of renewable energy sources and other distributed energy sources has been seen nowadays. In this scenario power converters play a crucial role by providing the interconnection of these energy sources. This paper presents new configurations of power converters for grid interconnection systems. Several topologies are analyzed which are based on isolated ac-ac matrix converters.